Pengaruh Motivasi, Komunikasi dan Stres Kerja terhadap Kepuasan Kerja Karyawan Outsource Universitas Ciputra - Fery Susanto; Dewi Mustikasari Immanuel (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Job satisfaction is an important element in determining organizational success, including for outsourced employees who face different working conditions compared to permanent employees, such as job status security, employment stability, and career development opportunities. This study aims to examine the effect of work motivation, communication, and work stress on the job satisfaction of outsourced employees at Universitas Ciputra. The research employs a quantitative approach with a sample of 95 outsourced employees. Data were collected through questionnaires and analyzed using t-tests, F-tests, and the coefficient of determination with the assistance of SPSS software. The results indicate that work motivation, communication, and work stress have a positive and significant effect on job satisfaction, both partially and simultaneously. These findings emphasize that increasing motivation through fair compensation systems and career development opportunities, implementing effective and open communication between supervisors and employees, and managing work stress properly can enhance the job satisfaction of outsourced employees. This study provides practical implications for management in designing more inclusive and sustainable human resource management policies and strategies.